Analisis kecemasan mahasiswa pendidikan matematika dalam menyusun tugas akhir - Hidayati, Ully (Jurnal Pendidik Indonesia, 2022)
Preparing for the final assignment is a student's obligation to obtain an academic degree from a tertiary institution. The final project is prepared following specific scientific procedures. However, sometimes some obstacles hinder the process and cause anxiety to students. This anxiety, if left untreated, can harm students and their studies. Thus, this study aims to describe the anxiety of students in the Mathematics Education Study Program, University of Sembilanbelas November Kolaka Class of 2019, in preparing their final assignment. This type of research is descriptive and qualitative, involving 26 students. The selected students are students who are currently preparing their final project to be in line with the objectives of this research. Data collection was obtained through the distribution of questionnaires and individual interviews. Data analysis was done through data reduction techniques, data presentation, and conclusion. The results showed that the factors that influence student anxiety are internal factors, including students' lack of confidence in their abilities, laziness and lack of discipline. At the same time, external factors come from the supervising lecturer's condition and the parents' economic conditions.